Developing and validating quantitative food frequency questionnaire to assess dietary vitamin D intake among adults in Indian population - M Annie Monica Priyadharshini; G Gayathri; Shriraam Mahadevan (Wolters Kluwer Medknow Publications, 2024)
The objective of this study is to create and validate a quantitative food frequency questionnaire (FFQ) for the assessment of Vitamin D intake among adults in Indian population. A quantitative FFQ was developed consisting of Vitamin D dietary-rich sources selected from IFCT, 2017. Further, the FFQ was validated against 24-h dietary recall from randomly selected 385 adults, both men and women above 25 years of age. The mean dietary Vitamin D intake estimated using quantitative FFQ was 402.61 ± 101.21 IU/day and that from 24-h dietary recall was 392.83 ± 120.86 IU/day. The coefficient of correlation between these two methods was 0.86 (P < 0.001) suggestive of high correlation between the two dietary assessment tools. This indicates that Vitamin D intake from FFQ and 24-h recall was similar. This efficient FFQ can assess adult Vitamin D intake in epidemiological studies, offering convenience, and ease of evaluation.